Role of Voglibose in the Treatment of Prediabetes in Indian Population: A Cross-Speciality Survey - Pavitra Raj Dewda; Sourabh Agrawal (Journal of Clinical and Diagnostic Research, 2013)
Background: Prediabetes is a precursor of overt Type 2 Diabetes Mellitus (DM) and it is associated with insulin resistance and an increased risk for cardiovascular disease. ACE and AACE recommend only lifestyle modifications for the management of prediabetes. A recently published meta-analysis suggested that drug therapy was associated with a better control of diabetes. Voglibose was recently approved for the management of prediabetes in Japan. Material and Methods: A well-structured questionnaire was sent to 117 doctors across India (52 diabetes specialists, 45 general practitioners, and 20 specialists from other branches of medicine) to understand their views on the management of prediabetes, especially with regards to voglibose. Results and Conclusion: There was an equivocal response to the question as to whether only diet and exercise were sufficient for the management of prediabetes. Most of the respondents used metformin for the management of prediabetes, while voglibose was the most favoured second-line drug. Almost all the respondents agreed that the approval which voglibose got in Japan for the management of prediabetes was relevant in India as well. Only 51.3% of all respondents had prescribed voglibose for prediabetes. Thus, voglibose appears to be popular secondline drug for the management of prediabetes.